2015
DOI: 10.1017/s1368980015000956
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a nutrition education programme on clinical status and dietary behaviours of adults with type 2 diabetes in a resource-limited setting in South Africa: a randomised controlled trial

Abstract: Objective: To evaluate the effect of a participant-customised nutrition education programme on glycated Hb (HbA 1c ), blood lipids, blood pressure, BMI and dietary behaviours in patients with type 2 diabetes mellitus. Design: A randomised controlled trial. The control group (n 41) received education materials. The intervention group (n 41) received the same education materials and participated in eight weekly (2-2·5 h) group nutrition education sessions and follow-up sessions. Outcomes were assessed at 6 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
165
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(174 citation statements)
references
References 61 publications
6
165
2
1
Order By: Relevance
“…The findings indicated high participant programme satisfaction, as well as perceived or real benefits from participating in the study. Although significant clinical and some dietary outcomes were not achieved in the main study, 12 it was indicated through the qualitative arm of the study that participants believed that they had benefited in diverse ways. Thus, the findings highlight the limitations of using quantitative measures only to assess the effect of an intervention.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The findings indicated high participant programme satisfaction, as well as perceived or real benefits from participating in the study. Although significant clinical and some dietary outcomes were not achieved in the main study, 12 it was indicated through the qualitative arm of the study that participants believed that they had benefited in diverse ways. Thus, the findings highlight the limitations of using quantitative measures only to assess the effect of an intervention.…”
Section: Discussionmentioning
confidence: 88%
“…The ability to visualise what was taught (from the visual tools, materials and food displays) could have contributed to the significant finding on reduced starchy food intake (servings) in the intervention group. 12 Strengths and limitations of the study Process evaluation, nested in a randomised controlled trial, was employed in this study. Therefore, insight was gained into participants' experience of the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intervention descriptions included in the 53 publications were assessed for completeness and replicability using the TIDieR checklist . The studies by Gagliardino et al .…”
Section: Resultsmentioning
confidence: 99%